Invasive Plant Ecology - Jose, Shibu; Singh, Harminder Pal; Batish, Daizy Rani; Kohli, Ravinder Kumar (CRC Press, 2013)
Comprising a series of essays from botanical experts across the globe, this reference presents a comprehensive examination of the problem of invasive plant species and their impacts on different ecosystems. Through examination of ecological theories that explain plant invasions, it provides a foundation in invasion ecology. Contributors discuss the role of ecological attributes such as plant life history and fire and management practices with respect to plant invasion. The book examines the physiological basis for invasive species success and gives ecological management and restoration guidelines for invaded areas.